Does Current General Mental Health Status Relate to Current Smoking Status in Pregnant Women? - Diane Liu; Emily Younger; Stacy Baker; Stephanie Touch; Tamara Willmoth; Jessica L. Hartos (Journal of Pregnancy)
Purpose. Research shows that smoking during pregnancy is related to mental health diagnoses. The purpose of this study was to assess whether current general mental health status is related to current smoking status in pregnant women after controlling for other factors related to both mental health and tobacco use during pregnancy. Methods. This cross-sectional analysis used 2017 Behavioral Risk Factor Surveillance Survey (BRFSS) data for 621 pregnant women aged 18-38 from Florida (N=136), Kansas (N=116), Minnesota (N=105), Nebraska (N=90), New York (N=78), and Utah (N=96). Multiple logistic regression analysis was used to assess the relationship between current mental health status and current tobacco use, while controlling for state, depression diagnosis, routine checkup, healthcare plan, age, marital status, ethnicity/race, education level, income level, and employment status. Results. Overall, very few participants reported current smoking (6%) and about one-third reported low or moderate mental health status in the past 30 days. Adjusted results indicated that those who reported high mental health status were about 3 times less likely (OR=0.29, 95% CI=0.09, 0.88) to report current smoking status compared to those who reported low mental health status. Conclusions. Overall, current mental health status was highly related to current smoking status in pregnant women. Clinicians in obstetrics may expect a very low proportion of pregnant women to report smoking and up to one-third to report low or moderate current general mental health status. Given that current mental health issues and current tobacco use may harm both mother and child, be highly related in pregnant women, and change throughout the pregnancy, pregnant women should be screened automatically for both at each visit.